Gené, M. y Vommaro, G. (2023). El sueño intacto de la centroderecha y sus dilemas después de haber gobernado y fracasado. Buenos Aires: Siglo XXI Editores - Berardi Spairani, Adrián Pablo (2023)
Revista sin referato